(untitled) (International Journal of Engineering and Computer Science, 2018)
Health is important in many areas of life, both for people and companies. Healthy conditions will enhance work arousal and work ability and other abilities. With the rapid development of banks in Indonesia, among others, marked by the number of emerging banks, it is necessary a supervision of these banks. In this case Bank Indonesia as the central bank requires a control over the banks to know how the financial condition and business activities of each bank. Bank policies issued and implemented by Bank Indonesia are basically aimed at creating and maintaining health, both individually and banking as a system. The health or financial and non-financial condition of the bank is in the interest of all parties concerned, whether the owners, managers (management) of the bank, the community using bank services (customers) and Bank Indonesia as the supervisory authority of banks and other parties. The condition of the bank may be used by such parties to evaluate the bank’s performance in applying prudential principles, compliance with applicable regulations and risk management. The development of the banking industry, especially the increasingly complex and diverse products and services will increase the risk exposure facing banks. The problems that arise in the general public is the absence of tools or information system applications how carannya know that the bank where they save the funds is the bank in a healthy condition. Referring to these issues we will create a Prototype Application of Banking Health Assessment Using Camels And Rgec Methods, the source of data to be used comes from the data of banking financial statements by OJK informed to the public. Our research is a kind of applied research (Applied Research). The results can be directly applied to solve the problems encountered. In this research will be made Prototype Application of Banking Health Assessment Using Camels And Rgec Method With Utilization of Data Financial Reports of OJK Banking. The results of the prototype of the application is expected to be used to measure the health of a bank.